CONTRIBUTION TO FAUNA OF SAPROXYLIC ROVE BEETLES (COLEOPTERA: STAPHYLINIDAE) IN CONIFEROUS FORESTS OF THE CARPATHIAN NATIONAL NATURE PARK - Motruk, Yu. B.; Diedus, V. I.; Chumak, M. V.; Kyselyuk, O. I.; Krivosheyev, R. E.; Drogvalenko, O. M.; Glotov, S. V. (НДУ ім. М. Гоголя, 2025)
Saproxylic beetles are insects that depend on dead and decaying wood for at least part of their lifecycle and play an important ecological roles in European ecosystems. Together with fungi, they contribute to the destruction of deadwood as well as are involved in decomposition processes and the recycling of nutrients in natural ecosystems. The family rove beetles Staphylinidae is one of the largest families of beetles. Many species of the family Staphylinidae are characterized by high abundance, a clear allocation to certain natural habitats, and the ability to respond sensitively to changes in the environment, which allows them to be used as objects for bioindication of environmental pollution processes and monitoring of ecosystems. The aim of the study is to investigate the diversity of saproxylic beetles (Coleoptera, Staphylinidae) in primeval fir forest of the Carpathian National Nature Park. The report is based on the results of observations and collections which were conducted in coniferous forests of the Carpathian National Nature Park in 2023–2024. All traps were set up and operated yearly during the vegetation season from early April to late September. The community of saproxylic rove beetles collected in coniferous forests of the Carpathian National Nature Park is characterized by a high level of faunal diversity. The fauna of saproxylic rove beetles accounts for 217 species, of which 127 species are obligate or facultative saproxylic. The community of rove beetles collected in coniferous forests of the Carpathian National Nature Park is characterized by a high level of faunal diversity. The result of our research is a section of the composition of the beetle community at a certain stage of forest succession. In the future, these data can be used by researchers to assess other territories, in particular with the aim of forming proposals for rational sustainable forest use, which Ukrainian forestry is gradually moving towards. The presented taxonomic list does not claim to be comprehensive, but it serves as a basis for further inventorying and monitoring the diversity of saproxylic beetles, as well as maintaining a cadastre of natural complexes in the Carpathian National Nature Park
Keywords: Coleoptera; Staphylinidae; saproxylic species; coniferous forests; fauna